2016
DOI: 10.18203/2349-2902.isj20164450
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and management of cholelithiasis in children: a hospital based study

Abstract: INTRODUCTIONCholelithiasis is quite common in adults (10% to 20%) with worldwide variability. In India, it is 3% to 6%, more frequent in north India than in south India.1 As far as cholelithiasis in children is concerned there is a dramatic change in the overall spectrum of this disease with global increase in the incidence.2 Overall prevalence in Europe is 0.13% to 0.2% in children. In Japan, it is less than 0.13% of children & about 0.3% in India.3,4 Childhood cholelithiasis is evolving with an ever increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Although Gibson reported the first case of paediatric cholelithiasis as early as 1737, it was found to be an uncommon pathology in children 5 . Recently however, several investigators have reported an increase in its frequency and the resultant cholecystectomy [6][7][8][9] . Incidence of gallstone disease in India is 0.3% with less than 0.1% in the 0-10 year age group 10,11 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although Gibson reported the first case of paediatric cholelithiasis as early as 1737, it was found to be an uncommon pathology in children 5 . Recently however, several investigators have reported an increase in its frequency and the resultant cholecystectomy [6][7][8][9] . Incidence of gallstone disease in India is 0.3% with less than 0.1% in the 0-10 year age group 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Risks of laparoscopic cholecystectomy include CBD injury, bile leak, bleeding, wound infection, retained stones. Several series report minimal complication rates 7,12,18 . St Peter et al 19 and Tannuri AC, et al 20 , in their studies reported no conversions, ductal injuries, bile leaks, or deaths.…”
Section: Usg Of Abdomen Especially Of Hepato-biliary Region Remains the Mainstay Of Diagnosis In Cholelithiasismentioning
confidence: 99%
See 2 more Smart Citations
“…Literatürle uyumlu şekilde karın ağrısı hastaların 37'sinde (%46,8) olmak üzere en sık gözlenen semptomdu. 9,15,16 Hastalarımızın % 24'ünde taş boyutu >1 cm idi. Taş boyutu 1 cm'nin üzerinde olan hastaların 6'sında obezite, 3'ünde hemolitik anemi ve 4'ünde seftriakson kullanımı öyküsü mevcuttu.…”
Section: Gereç Ve Yöntemunclassified